From dictatorship to democracy : a conceptual framework for liberation - Sharp, Gene, 1928-2018 (New Press, 2012)
Twenty-one years ago, at a friend's request, a Massachusetts professor sketched out a blueprint for nonviolent resistance to repressive regimes. It would go on to be translated, photocopied, and handed from one activist to another, traveling from country to country across the globe: from Iran to Venezuela -- where both countries consider Gene Sharp to be an enemy of the state -- to Serbia; Afghanistan; Vietnam; the former Soviet Union; China; Nepal; and, more recently and notably, Tunisia, Egypt, Yemen, Libya, and Syria, where it has served as a guiding light of the Arab Spring. This short guide to overthrowing a dictatorship by nonviolent means lists 198 specific methods to consider, depending on the circumstances: sit-ins, popular nonobedience, selective strikes, withdrawal of bank deposits, revenue refusal, walkouts, silence, and hunger strikes.